Physical stability against hydrogen plasma for ZnInSnO thin films deposited by combinatorial RF magnetron sputtering. (16th November 2016) - Kim, Eun Mi; Oh, Jeung-Pyo; Ha, Tae-Won; Kim, Young-Baek; Kim, Tae-Won; Heo, Gi-Seok
Abstract: We investigated the physical stability of ZnInSnO thin films against hydrogen plasma using a plasma-enhanced chemical vapor deposition (PECVD) system. The transmittance and resistivity characteristics of the entire ZnInSnO films showed very little degradation after the hydrogen plasma treatment. However, the deposited films with a zinc content of ≤8.8 at. % [Zn/(In + Sn + Zn), at. %] showed some optical and electrical property degradation. Within this compositional range, the resistivity of the films treated with hydrogen plasma increased compared with that of the as-deposited films. For the film with a zinc content of 7.6 at. %, the transmittance decreased by 21% compared with that of the as-deposited ZnInSnO film (at a standard optical wavelength of 2000 nm). The figure of merit of the deposited ZnInSnO thin films with a zinc content of >8.8 at. % was physically stable against hydrogen plasma. We found that the deposited ZnInSnO thin films with a zinc content above 8.8 at. % have high physical stability against hydrogen plasma.